The impact of cultural beliefs and practices on parents' experiences of bereavement following stillbirth: a qualitative study in Uganda and Kenya - Elizabeth Ayebare; Tina Lavender; Jonan Mweteise; Allen Nabisere; Anne Nendela; Raheli Mukhwana; Rebecca Wood; Sabina Wakasiaka; Grace Omoni; Birungi Susan Kagoda; Tracey A. Mills (BMC, 2021)
Abstract Background Stillbirth is an extremely traumatic and distressing experience for parents, with profound and long-lasting negative impacts. Cultural beliefs and practices surrounding death vary considerably across different contexts and groups, and are a key influence on individual experiences, impacting grief, adjustment, and support needs. Few studies have explored cultural influences surrounding stillbirth in an African context. This study explored the influence of cultural beliefs and practices on the experiences of bereaved parents and health workers after stillbirth in urban and rural settings in Kenya and Uganda. Methods A qualitative descriptive study design was employed. Face to face interviews were conducted with parents (N = 134) who experienced a stillbirth (≤ 1 year) and health workers (N = 61) at five facilities in Uganda and Kenya. Interviews were conducted in English or the participants' local language, audio-recorded and transcribed verbatim. Analysis was conducted using descriptive thematic analysis. Results Commonalities in cultural beliefs and practices existed across the two countries. Three main themes were identified: 1) Gathering round, describes the collective support parents received from family and friends after stillbirth. 2)'It is against our custom' addresses cultural constraints and prohibitions impacting parents' behaviour and coping in the immediate aftermath of the baby's death. 3) 'Maybe it's God's plan or witchcraft' summarises spiritual, supernatural, and social beliefs surrounding the causes of stillbirth. Conclusions Kinship and social support helped parents to cope with the loss and grief. However, other practices and beliefs surrounding stillbirth were sometimes a source of stress, fear, stigma and anxiety especially to the women. Conforming to cultural practices meant that parents were prevented from: holding and seeing their baby, openly discussing the death, memory-making and attending the burial. The conflict between addressing their own needs and complying with community norms hindered parents' grief and adjustment. There is an urgent need to develop culturally sensitive community programmes geared towards demystifying stillbirths and providing an avenue for parents to grieve in their own way.